Exosomes in the f ield of reproduction: A scientometric study and visualization analysis - Yifeng Shen; Yifeng Shen; Yaodong You; Yaodong You; Kun Zhu; Chunyan Fang; Degui Chang; Degui Chang; Xujun Yu (Frontiers Media S.A., 2022)
Background: The diagnostic capabilities of exosomes in the field of reproductive biomedicine have attracted much attention. The aim of this scientometric study was to statistically and qualitatively assess the knowledge structure, hot issues, and research trends of papers about exosomes in the field of reproduction using visualization methods.Methods: The Web of Science Core Collection was searched for studies on exosomes in the field of reproduction. We performed bibliometric and visual analyses using VOSviewer, CiteSpace, and Microsoft Excel.Results: After database search, 1,011 articles were included, with number of studies being published every year continually increasing. These publications came from 61 nations or regions, with the US having the highest number. The University of Queensland was the main institution in which the research was conducted. The journal Placenta contained the highest number studies. There were 5,247 authors in total. Carlos Salomon had the highest number of papers with co-citations. Exosomes, extracellular vesicles, pregnancy, microRNAs, preeclampsia, placenta, microvesicles, gene expression, biomarkers, and first trimester were the most frequently used terms.Conclusion: Exosome research is booming in reproductive biomedicine. Future studies will likely focus on exosomes as biomarkers in gamete formation and fertilization, pregnancy, and cancers associated with reproduction. In addition to focusing on fundamental research, we should concentrate on the application of the results and the investigation of exosomes in infertile patients.